A Review of Energy Demands and its’ Implication on Climate Change in Africa - (:unkn) unknown (My University, 2024)
Climate change is one of the most pressing issues facing the world today. Communities around the world are already feeling its effects, and the situation is only expected to get worse in the future. One of the sectors particularly vulnerable to climate change's effects is the energy sector. In many African countries, the energy sector is heavily reliant on fossil fuels. This makes African countries particularly susceptible to the effects of climate change, as the availability of fossil fuels is expected to decrease in the future because of climate change. This could lead to higher energy prices and a decrease in the availability of energy. In addition, climate change is expected to have a significant impact on hydropower, which is another important source of energy in many African countries. Changes in rainfall patterns could lead to lower river levels and reduced hydroelectric power generation. This could have a severe impact on the availability of energy in African countries. The effects of climate change on the energy sector are likely to have a knock-on effect on the wider economy. Higher energy prices could lead to inflation and a decrease in the availability of energy which could lead to blackouts and a decrease in production. This could have a devastating impact on the economies of African countries. The effects of climate change on the energy sector are likely to be very damaging for African countries. These countries need to take action to mitigate the effects of climate change and to adapt their energy systems to cope with the changes that are expected to occur. This review outlines the climate change impacts on the energy sector in African countries and recommendations to mitigate the effects of climate change impacts.
Keywords: African Research